2021
DOI: 10.1021/acs.jpcc.1c02531
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Experiment for Oxygen Isotope Exchange over Copper-Containing Mordenite

Abstract: Oxygen isotope exchange for sodium- and copper-containing mordenite was studied in the isothermal regime using a plug-flow reactor. No prominent exchange was observed over sodium mordenite at 873 K. In contrast, the presence of copper significantly increases the lability of oxygen atoms resulting in a substantial rate of isotope exchange in the temperature range between 793 and 873 K. A novel numerical model accounting for two kinetically distinct sources of exchangeable oxygen atoms was proposed and shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…As reported by Leglise et al, FeMOR has around 34% of the exchangeable oxygen atoms at 773 K. Similar values were obtained in our recent study on oxygen isotope exchange over copper-containing mordenite . Notably, the sodium and proton forms of zeolites do not undergo the isotope exchange under similar conditions at a prominent rate, , showing that the hosted metal species induce the lability of the framework oxygen atoms. Importantly, the mechanism of the exchange depends significantly on the nature of the hosted species.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…As reported by Leglise et al, FeMOR has around 34% of the exchangeable oxygen atoms at 773 K. Similar values were obtained in our recent study on oxygen isotope exchange over copper-containing mordenite . Notably, the sodium and proton forms of zeolites do not undergo the isotope exchange under similar conditions at a prominent rate, , showing that the hosted metal species induce the lability of the framework oxygen atoms. Importantly, the mechanism of the exchange depends significantly on the nature of the hosted species.…”
Section: Introductionsupporting
confidence: 91%
“…Depending on the number of oxygen atoms from the solid phase participating in the exchange reaction, zero-atom (R 0 ), single-atom (R 1 ), and two-atom (R 2 ) kinetically distinct types of exchange were suggested. We previously showed that the isothermal oxygen isotope exchange over copper-containing mordenite can be adequately described using the kinetic model with two independent sources of exchangeable oxygen, which undergo both R 1 and R 2 types of exchange . The corresponding set of partial differential equations (PDE) is as follows with the following initial and boundary conditions where C­(O 2 ) gas represents the concentration of the oxygen molecules in the gas phase; α fast and α slow are the fraction of 18 O atoms in the “fast” and “slow” source, respectively; and C­(O) (mol·L –1 ), k 1 (L·mol –1 ·s –1 ) and k 2 (L 2 ·mol –2 ·s –1 ) are the concentration of exchangeable oxygen atoms and kinetic constants of single-atom and two-atom exchange, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations